Nonlinear Height-Stump Diameter Models for Tectona grandis Linn. F Stands in Omo Forest Reserve, Nigeria - Chukwu, O.; Osho, J.S.A. (Journal of Tropical Forestry and Environment, 2017)
Illegal exploitation of timber species in developing countries have increased over the years. Though, there is dearth of empirical models for describing the dimension, structure, quality and estimating quantity of a removed tree needed for assessment of damage due to catastrophic events, creating historical records of previous management activities and for conviction of illegal loggers. The objective of this study was to develop and test non-linear models that can effectively estimate individual tree merchantable height (Ht) from stump diameter (Ds) for Tectona grandis stands in Omo Forest Reserve, Nigeria, for timber valuation in case of illegal felling. Thirty-six temporary sample plots (TSPs) of size 25 m x 25 m were laid randomly in six age strata of T. grandis; 26, 23, 22, 16, 14, and 12 years specifically. Diameter at breast height, Ht and Ds were measured for all living T. grandis trees within the 36 TSPs. Least square method was used to convert the counted stumps into harvested stem height. Four Ht-Ds models were fitted and evaluated. The Ht-Ds relationship was best described by square model which gave least values of root mean square error (0.083) and Akaike information criterion (-7578). This study revealed that height estimation was realistic even when the only information available was stump diameter. The square model was validated using independent data not used in the model calibration and was found to be appropriate for estimating the height of T. grandis stands in Omo Forest Reserve, Nigeria. Keywords: Tree height, Nonlinear model, Stump diameter, Square, Tectona grandis